2009
DOI: 10.1016/j.drugalcdep.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Screening, brief interventions, referral to treatment (SBIRT) for illicit drug and alcohol use at multiple healthcare sites: Comparison at intake and 6 months later

Abstract: Objectives-Alcohol screening and brief interventions in medical settings can significantly reduce alcohol use. Corresponding data for illicit drug use is sparse. A Federally funded Screening, Brief Intervention, Referral to Treatment (SBIRT) service program, the largest of its kind to date, was initiated by the Substance Abuse and Mental Health Services Administration (SAMHSA) in a wide variety of medical settings. We compared illicit drug use at intake and six months after drug screening and interventions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
504
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(517 citation statements)
references
References 77 publications
9
504
1
3
Order By: Relevance
“…Madras et al [1] noted that response rates were particularly low in two projects, one due to program interruption and the other to a significant shift in the program's follow-up model. We therefore calculated alternative response rates that were adjusted based on the timing of these events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Madras et al [1] noted that response rates were particularly low in two projects, one due to program interruption and the other to a significant shift in the program's follow-up model. We therefore calculated alternative response rates that were adjusted based on the timing of these events.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up interviews were conducted between 150 and 240 days after baseline screening and were administered either in person or by telephone. As noted in Madras et al [1] most were by telephone because projects found it difficult to have patients return to the original site after 6 months.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…3,[38][39][40][41][42][43] When a patient endorses pain, the physician must first determine the etiology of the pain and then decipher if the patient has risk factors for aberrant opioid use. The physician must then identify an appropriate treatment strategy for pain control, which may or may not include opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, there is a need for more evidence on effective interventions for substance using patients in acute care settings. A service program including screening, brief interventions and referral to treatment has shown very promising results with regard to substance use and related problems in a wide range of medical settings (110). Similar programs could be implemented and evaluated in acute psychiatric services as well.…”
Section: Clinical Implications and Future Researchmentioning
confidence: 99%